2022
DOI: 10.1002/brb3.2568
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential wall enhancement with contrast ratio measurement in unruptured intracranial aneurysm for aneurysm instability

Abstract: Background Aneurysm wall enhancement on high‐resolution vessel wall imaging (HR‐VWI) may represent vessel wall inflammation for unruptured intracranial aneurysms (UIAs). Further evidence for the role of circumferential aneurysm wall enhancement (CAWE) in evaluating the instability of UIAs is required, especially in small aneurysms (<7 mm). Methods We analyzed patients with saccular UIAs who prospectively underwent HR‐VWI on a 3.0 T MRI scanner in our center from September 2017 to August 2021. The presence of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In a study of 19 patients harboring 22 unruptured IAs, there was a significant association of CRstalk ≥0.5 with decreased plasma concentration of the anti-inflammatory cytokine IL-10 in the aneurysm sac ( 19 ). In our previous study, the optimal cutoff value of CRstalk for circumferential AWE was 0.5 ( 24 ). We found that the level of NLR at admission and aneurysm size was associated with CRstalk ≥0.5 in 57 patients with 60 unruptured IAs in the current study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In a study of 19 patients harboring 22 unruptured IAs, there was a significant association of CRstalk ≥0.5 with decreased plasma concentration of the anti-inflammatory cytokine IL-10 in the aneurysm sac ( 19 ). In our previous study, the optimal cutoff value of CRstalk for circumferential AWE was 0.5 ( 24 ). We found that the level of NLR at admission and aneurysm size was associated with CRstalk ≥0.5 in 57 patients with 60 unruptured IAs in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, quantitative measurement of AWE on HR-VWI has been used to avoid the subjectivity of the readers ( 19 , 24 , 26 ). CRstalk using maximal SI may be a new tool to predict the instability of unruptured IA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations